The use of terrestrial and airborne LIDAR technology in forest inventory / O uso da tecnologia LIDAR aerotransportado e terrestre no inventário ﬂorestal - Tomasz Zawila-Niedzwiecki; Krzysztof Sterenczak; Radomir Balazy; Agata Wencel; Pawel Strzelinsk; Michal Zasada (Ambiência, 2008)
Paper describes Polish experiences with the use of terrestrial andairborne LIDAR in forestry and especially in forest inventory. Two types of airborne scanners (TopoSys and Optech) were used to visualise two different test sites: one located on ﬂ at terrain and another in the mountains. For terrestrial scanning FARO LS880 laser equipment was used. LIDAR data were related to precise forest inventory parameters of stands and trees.